2011
DOI: 10.1371/journal.pone.0027950
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Cellular Logistics of Collective Cell Migration

Abstract: During development, the formation of biological networks (such as organs and neuronal networks) is controlled by multicellular transportation phenomena based on cell migration. In multi-cellular systems, cellular locomotion is restricted by physical interactions with other cells in a crowded space, similar to passengers pushing others out of their way on a packed train. The motion of individual cells is intrinsically stochastic and may be viewed as a type of random walk. However, this walk takes place in a noi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…To investigate whether these observed traffic rules on the individual cell level indeed do cause the very varied collective motion we observed, we formulated an agent-based mathematical model using the simplest physically reasonable assumptions for the motion of the individual cell based on three types of input: (i) our own pseudopod observations, (ii) previous experimental studies on chemotaxis of isolated cells, and (iii) Newton's second law of particle motion (SI Appendix, Model Details). This model, which can be considered an extension of the Vicsek model (21,22,42), exploits known cellular biophysics to simulate our experiments with a few hundred cells, a regime that is inaccessible to continuum modeling (43,44). Model cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate whether these observed traffic rules on the individual cell level indeed do cause the very varied collective motion we observed, we formulated an agent-based mathematical model using the simplest physically reasonable assumptions for the motion of the individual cell based on three types of input: (i) our own pseudopod observations, (ii) previous experimental studies on chemotaxis of isolated cells, and (iii) Newton's second law of particle motion (SI Appendix, Model Details). This model, which can be considered an extension of the Vicsek model (21,22,42), exploits known cellular biophysics to simulate our experiments with a few hundred cells, a regime that is inaccessible to continuum modeling (43,44). Model cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is shown below through a number of statistical tests. Although simpler theoretical models have been presented in the past with the objective of investigating certain traits of the collective migration phenomena (21,22,37,(42)(43)(44)(45), none of these models is able to simultaneously account for a wide variety of the migration data such as ours, and our model thus provides one of the simplest ways of incorporating all of our observations in a physically transparent formulation.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, skewing away from Vicsek's alignment to neighboring cells behavior, this model includes cells that align to the direction of the net force acting upon them. This model was then further improved to investigate the migration behavior of cells [156][157][158][159] . The results revealed that cell packing fraction, moving velocity and noise level controlled whether the cells migrated as collective or dispersive behavior.…”
Section: Self-propelled Particle (Spp) Modelmentioning
confidence: 99%
“…For collective cell migration, we can distinguish between two categories of computational models: (i) the agent-based models (AGMs) and (ii) the continuum models (CMs). AGMs simulate the activity and the interactions of cells within a population and assess their influence on the global system by taking into account the rate of cell division, the cell proliferation, the adhesion between the cells and the substrate, the deformation energy, and the stochastic behavior of the cellular collective (Graner and Glazier 1992;Szabo et al 2006;Vedel et al 2013;Vicsek et al 1995;Yamao et al 2011).…”
Section: Numerical Models Of Collective Cell Migrationmentioning
confidence: 99%
“…A few models (McLennan et al 2012;Yamao et al 2011) describe the collective migration focusing on the movement of the neural crest, which occurs in the absence of extracellular signals.…”
Section: Numerical Models Of Collective Cell Migrationmentioning
confidence: 99%